1996
DOI: 10.1017/s0022029900031757
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory activities of whey fractions in efferent prefemoral lymph of sheep

Abstract: SummaryStudies on the immunomodulatory activities of ruminant milk and colostral whey fractions were undertaken. By comparing with boiled colostral whey in a preliminary experiment, a putative heat-labile immunostimulatory factor for antibody responses was found to be present in ovine colostral whey. Studies were then undertaken in sheep in which the efferent prefemoral lymphatic ducts were cannulated bilaterally, and immune responses in the node were measured following subcutaneous injection in the flank fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…In addition to economic loss, the current methods of disposal of whey create environmental problems; 100 l of whey has the polluting strength of sewage from 45 people (Brown, 1984). Therefore, during the past decade there has been increased interest in finding new economic uses for whey (Wong et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to economic loss, the current methods of disposal of whey create environmental problems; 100 l of whey has the polluting strength of sewage from 45 people (Brown, 1984). Therefore, during the past decade there has been increased interest in finding new economic uses for whey (Wong et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these proteins have been found to possess a variety of bio-active properties including modulation of the immune system (Stoeck et al, 1989;Mincheva-Nilsson, 1990;Wong et al, 1996Wong et al, , 1997Barta 1991;Monnai et al, 1998). Furthermore, minor changes in dietary amino acid profile, due to consumption of different whey protein mixtures, have been found to modify the immune response without having a significant impact on nutritional status (Bounous & Kongshavn, 1978), suggesting that different WPC preparations can have different effects on the immune system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown LPO induces tumor necrosis factor production by macrophages [18] and suppresses interferon (IFN)-γ production by mitogen-stimulated lymphatic cells [19]. Subcutaneously injected LPO reduces efferent lymphocyte output and lymph flow rate in the local lymph nodes of sheep [20]. We found orally administered LPO suppressed symptoms of pneumonia in mice infected with the influenza virus through inhibition of inflammatory cells in the lung and pro-inflammatory cytokines [21]; LPO also upregulated genes inducible by glucocorticoid, a steroidal hormone with anti-inflammatory activity, in the small intestine of mice [22].…”
Section: Introductionmentioning
confidence: 99%
“…10) Reduced lymphocyte output and lymph flow rate from the local lymph nodes have also been observed in sheep after LPO was injected subcutaneously. 11) There have been few reports on the physiological effects of orally administered LPO, but we recently examined the effect of LPO treatment in a model of pneumonia caused by influenza virus infection in mice.…”
mentioning
confidence: 99%